2005
DOI: 10.1016/j.nuclcard.2005.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of myocardial perfusion imaging in a study population without post-test referral bias

Abstract: In this prospective study without post-test referral bias, we found a lower sensitivity and slightly higher specificity than in studies with post-test referral bias. The imperfect accuracy may reflect differences between anatomic and physiologic imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 45 publications
0
24
0
2
Order By: Relevance
“…Since the prevalence of obstructive CAD (C70% stenosis) in the 208 patients included in the study was high (68.8%), the data of additional 76 patients with very low 10-year risk, who did not have ICA were included. 23 Using the QPS software with custom-developed normal limits, quantitative stress-TPD from supine and prone acquisitions yielded high diagnostic values (AUC [ 0.9) in both patient subgroups. Sensitivities were high in the lowdose and standard-dose subgroups (86.1% and 90.6%, respectively, P = ns) with lower specificities (76.6% and 78.1%, P = ns), reflecting post-test referral bias to ICA.…”
Section: Discussionmentioning
confidence: 99%
“…Since the prevalence of obstructive CAD (C70% stenosis) in the 208 patients included in the study was high (68.8%), the data of additional 76 patients with very low 10-year risk, who did not have ICA were included. 23 Using the QPS software with custom-developed normal limits, quantitative stress-TPD from supine and prone acquisitions yielded high diagnostic values (AUC [ 0.9) in both patient subgroups. Sensitivities were high in the lowdose and standard-dose subgroups (86.1% and 90.6%, respectively, P = ns) with lower specificities (76.6% and 78.1%, P = ns), reflecting post-test referral bias to ICA.…”
Section: Discussionmentioning
confidence: 99%
“…In this population, the overall sensitivity of MPS was found to be 75% and the specificity was 79% (8). At publication, these results were attributed to the absence of a referral or work-up bias.…”
mentioning
confidence: 68%
“…This study has a number of companion publications (6)(7)(8); the purpose of the original study was to compare patient findings on MPS with those found on CA. In this population, the overall sensitivity of MPS was found to be 75% and the specificity was 79% (8).…”
mentioning
confidence: 99%
“…Final interpretation and overall diagnosis were determined by consensus. The diagnostic accuracy of this approach has been reported elsewhere (21). The MPS results were not revealed to the referring physician.…”
Section: Mpsmentioning
confidence: 80%
“…Both left ventricular hypertrophy (more than 75% of our study population had a history of hypertension) and microvascular disease may be associated with perfusion abnormalities in the presence of normal coronary arteries (21,30,31). The precise impact of these confounders remains unknown; however, hypertension does not degrade the diagnostic value of MPS for diagnosing coronary artery disease (32), and none of the factors can explain the high rate of insignificant angiographic disease in these patients.…”
Section: Discussionmentioning
confidence: 97%